GOOD GOVERNANCE DI BIDANG PEMERINTAHAN DALAM PERSPEKTIF OTONOMI DAERAH - Sugianto (Jurnal Ilmu Hukum Tambun Bungai, 2017)
In the era of reform As a tangible manifestation of the Implementation of Local Government by promoting the concept of decentralization, regional autonomy is the main topic that must be discussed and implemented in all the administrative arrangements of local government and society. Under Act No. 23 of 2014 in lieu of Law No. 32 of 2004 on Regional Governance, the present era is free from the complicity of executive and legislative interests. Because in the Implementation of Regional Head Election in this case the Governor, Regent and Mayor have become its own regulation that is Law no 10 year 2016, to choose clean regional leader and statesman as a real manifestation through local elections simultaneously "inevitably has become the people's right , But still there can not escape political interests because candidates for regional heads in the Act is carried by political parties or a combination of political parties. That in the current era of reformasi there are still problems to realize clean leader and statesmen. Of course, a healthy and clean Indonesian nation from corruption, collusion and nepotism is a sure thing of this good governance principle, and of course is something that Indonesian people really miss. The election of new leaders is part of the will of the people who want to create a capable Leader and promote synergy and Harmonization.